Análise dos registros de dose ocupacional externa no Brasil (Brazilian Journal of Radiation Sciences (BJRS), 2015)
Brazil, a continental country, with actually more than 150,000 workers under individual monitoring for ionizing radiation, has implemented in 1987 a centralized system for storage of external occupational dose. This database has been improved over the years and is now a web-based information system called Brazilian External Occupational Dose Management Database System - GDOSE. This paper presents an overview of the Brazilian external occupational dose over the years. The estimated annual average effective dose shows a decrease from 2.4 mSv in 1987 to about 0.6 mSv, with a remarkable reduction from 1987 to 1990. Analyzing by type of controlled practice, one sees that the medical radiology is the area with the largest number of users of individual monitors (60%); followed by educational practices (9%) and industrial radiography (8%). Additionally to photon whole body monitoring; neutron monitors are used in maintenance (36%), reactor (29%) and education (27%). Extremity monitors are mainly used in education (27%), nuclear medicine (22%) and medical radiology (19%). In terms of collective dose, the highest value is also found in medical radiology, but the highest average dose value is received by interventional radiology IOE. Nuclear medicine, radiotherapy and research practices present average annual effective dose higher than 1 mSv. However, some dose values higher than 500 mSv registered in the data base give false information. They are not realistic. This should be better analyzed in the future to improve the analysis of the trends of external occupational dose in Brazil.